Anne Scott Sørensen (red.): Nordisk salonkultur. Et studie i nordiske skønånder og salonmiljøer 1780-1850. Universitetsforlag, 1998). 493 s., 350 kr. - Morten Jessen, Jens (Historie/Jyske Samlinger, 1999)
-